Does the Severity of the Curve in Lenke 1 and 2 Adolescent Idiopathic Scoliosis Patients Affect the Distance and Position of the Aorta From Vertebra?. Issue 11 (1st June 2019) - Chiu, Chee Kidd; Lee, Keong Joo; Chung, Weng Hong; Chandren, Josephine Rebecca; Chan, Chris Yin Wei; Kwan, Mun Keong
Abstract : Study Design: Retrospective study of a prospectively-collected data. Objective: To determine whether the severity of the curve magnitude in Lenke 1 and 2 Adolescent Idiopathic Scoliosis (AIS) patients affects the distance and position of the aorta from the vertebra. Summary of Background Data: There were studies that looked into the position of the aorta in scoliotic patients but none of them documented the change in distance of the aorta to the vertebra in relation to the magnitude of the scoliosis. Methods: Patients with Lenke 1 and 2 AIS who underwent posterior spinal fusion using pedicle screw construct and had a preoperative computed tomography (CT) scan performed were recruited. The radiological parameters measured on preoperative CT scan were: Aortic-Vertebral Distance (AVD), Entry-Aortic Distance (EAD), Aortic-Vertebral angle (AVA), Pedicle Aorta angle/Aortic Alpha angle (α angle), and Aortic Beta angle (β angle). Results: Thirty-nine patients were recruited. Significant moderate to strong positive correlation was found between AVD and Cobb angle from T8 to T12 vertebrae (r = 0.360 to 0.666). The EAD was generally small in the thoracic region (T4–T10) with mean EAD of less than 30 mm. Among all apical vertebrae, the mean AVD was 5.9 ± 2.2 mm with significant moderate-strong positive correlation to Cobb angle (r = 0.580). The mean α angle was 37.7 ± 8.7° with significant weak positive correlation with Cobb angle (r = 0.325). Conclusion: The larger the scoliotic curve, the aorta was located further away from the apical vertebral wall. The aorta has less risk of injury from the left lateral pedicle screw breach in larger scoliotic curve at the apical region. The distance from the pedicle screw entry point to the wall of the aorta was generally small (less than 30 mm) in the thoracic region (T4–T10). Level of Evidence: 4 Abstract : This study aimed to find out whether the severity of the curve magnitude in Lenke 1 and 2 adolescent idiopathic scoliosis patients affects the distance and position of the aortic from the vertebra. We found that the larger the curve, the further away the aorta from the apical vertebra.